2006
DOI: 10.1080/08820130600634568
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the Promoter Region of the CD14 Gene and Susceptibility to Brucellosis

Abstract: A single-nucleotide polymorphism in the promoter region of the CD14 gene at position 159 has been implicated in susceptibility to infectious diseases. We sought to determine the association between CD14 C-159 T functional promoter polymorphism and brucellosis in Western Iranian population where the disease is endemic. The CD14 genotype was determined in 228 patients with brucellosis from a rural area and 129 healthy volunteers from the same area. The prevalence of genotype TT was significantly higher in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…CD-14 associated molecule is necessary for the cellular response in infections mediated by bacterial lipopolysaccharide, which activates monocytes for the expression of cytokines, growth factors, and procoagulatory factors [20]. Failure of interaction of lipopolysaccharide with CD-14 has been implicated in susceptibility to infectious diseases [21].…”
Section: Introductionmentioning
confidence: 99%
“…CD-14 associated molecule is necessary for the cellular response in infections mediated by bacterial lipopolysaccharide, which activates monocytes for the expression of cytokines, growth factors, and procoagulatory factors [20]. Failure of interaction of lipopolysaccharide with CD-14 has been implicated in susceptibility to infectious diseases [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to show the impact of the CD14-159C/T SNP on the risk of infectious diseases [9,18,[21][22][23]. To the best of our knowledge, there is only one study assessing the association of CD14, -159C/T polymorphism and brucellosis [22]. Haidari et al [22], in their study on brucellosis in a Western Iranian population have shown that the frequency of the TT genotype was higher in the patients than in controls (34.5% vs. 15.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the CD14-159C/T gene polymorphism has been examined in several inflammatory and infectious diseases including tuberculosis [8,9,21] , brucellosis [22] , Chlamydia pneumoniae infection [23,24] , Helicobacter pylori infection [25] , hepatitis B and C [26,27] and severe acute respiratory syndrome [28], but the results have been inconsistent and conflicting. Therefore, the current study aimed to evaluate the possible association between the CD14-159C/T (rs2569190) gene polymorphism and susceptibility to acute brucellosis in an Iranian population.…”
Section: Introductionmentioning
confidence: 99%
“…A possible answer to this question may be due to polymorphisms of the promoter region on the CD14 gene and allelic polymorphism of genes coding TLR 4. 28,29 Allelic polymorphism of these genes may cause different level and type of innate immune response to Brucella microorganisms in different patients with only rare cases of excessive activation of mononuclear cells accompanied by autoaggressive reactions.…”
Section: Case Reportmentioning
confidence: 99%